PENERAPAN GREEN PRACTICE DALAM MENDUKUNG PARIWISATA BERKELANJUTAN DI CASA AMAROOSSA LOUNGE JAKARTA: Pariwisata Berkelanjutan - Muhammad Surya Saleh; Asep Parantika (JURNAL BISNIS HOSPITALITI, 2025)
This study focuses on the implementation of green practices in Casa Amaroossa Lounge Jakarta as a step to support sustainable tourism in urban areas, and analyzes the application of POAC (Planning, Organizing, Actuating, and Controlling) managerial approaches to manage and improve the effectiveness of implementing green practices in hotel environments. This study uses a qualitative method with the aim of understanding the application of green practices in Casa Amaroossa Lounge Jakarta through observations, interviews, and supporting documentation. Data analysis was conducted using Miles and Huberman's interactive model with a POAC managerial approach to evaluate the effectiveness of planning, organizing, implementing, and monitoring in the implementation of sustainable practices in the hotel environment. The results of the study show that the implementation of green practices is carried out through energy and water efficiency, the use of environmentally friendly materials, grouped waste management, the provision of food based on local and organic ingredients, and donation activities that support the welfare of the surrounding community. With POAC management, this activity is carried out systematically and in a directed manner. Green practices are very important to be applied to urban hotels, because they play a role in reducing the negative impact of operational activities on the environment, improving the positive image of hotels, and supporting sustainable tourism in urban areas that have quite high environmental pressure